The COVID-19, tuberculosis and HIV/AIDS: Ménage à Trois - Udoakang, Aniefiok John; Djomkam Zune, Alexandra Lindsey; Tapela, Kesego; Nganyewo, Nora Nghochuzie; Olisaka, Frances Ngozi; Anyigba, Claudia Adzo; Tawiah-Eshun, Sylvia; Owusu, Irene Amoakoh; Paemka, Lily; Awandare, Gordon A.; Quashie, Peter Kojo (Frontiers in Immunology, 2023)
In December 2019, a novel pneumonic condition, Coronavirus disease 2019 (COVID- 19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), broke out in China and spread globally. The presentation of COVID-19 is more severe in persons with underlying medical conditions such as Tuberculosis (TB), Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) and other pneumonic conditions. All three diseases are of global concern and can significantly affect the lungs with characteristic cytokine storm, immunosuppression, and respiratory failure. Co-infections of SARS-CoV-2 with HIV and Mycobacterium tuberculosis (Mtb) have been reported, which may influence their pathogenesis and disease progression. Pulmonary TB and HIV/AIDS patients could be more susceptible to SARS-CoV-2 infection leading to lethal synergy and disease severity. Therefore, the biological and epidemiological interactions of COVID-19, HIV/AIDS, and TB need to be understood holistically. While data is needed to predict the impact of the COVID-19 pandemic on these existing diseases, it is necessary to review the implications of the evolving COVID-19 management on HIV/AIDS and TB control, including therapy and funding. Also, the impact of long COVID on patients, who may have this co-infection. Thus, this review highlights the implications of COVID-19, HIV/AIDS, and TB co-infection compares disease mechanisms, addresses growing concerns, and suggests a direction for improved diagnosis and general management.